2015
DOI: 10.1111/evo.12702
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and maintenance of haploid-diploid life cycles in natural populations: The case of the marine brown algaEctocarpus

Abstract: The evolutionary stability of haploid-diploid life cycles is still controversial. Mathematical models indicate that niche differences between ploidy phases may be a necessary condition for the evolution and maintenance of these life cycles. Nevertheless, experimental support for this prediction remains elusive. In the present work, we explored this hypothesis in natural populations of the brown alga Ectocarpus. Consistent with the life cycle described in culture, Ectocarpus crouaniorum in NW France and E. sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 76 publications
1
83
0
Order By: Relevance
“…A recent study in the Ectocarpus group has shown that haploid and diploid organisms also exhibit clear niche partitioning. However, mainly asexual populations also exhibit similar habitat usage25. Although brown algae are mainly marine species, rare cases of adaptation to fresh water have been reported26.…”
mentioning
confidence: 99%
“…A recent study in the Ectocarpus group has shown that haploid and diploid organisms also exhibit clear niche partitioning. However, mainly asexual populations also exhibit similar habitat usage25. Although brown algae are mainly marine species, rare cases of adaptation to fresh water have been reported26.…”
mentioning
confidence: 99%
“…, , Couceiro et al. ). Several causes can be considered for explaining the rare occurrence of parthenogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…High fertilization success (i.e., few unfused gametes) has been proposed as the cause of the rare parthenosporophytes (Peters and Müller , Couceiro et al. ). It is well known that brown algae have various mechanisms that enhance the probability of gamete encounter, such as synchronous gamete release, phototaxis, and attraction of male gametes by sexual pheromones (Brawley and Johnson ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work on the life cycles of Ectocarpus species under field conditions suggests that the sporophyte generation tends to persist for longer and to be the stage of the life cycle that allows the species to overwinter (Couceiro et al, 2015). The gametophyte generation, by contrast, tends to be ephemeral during the spring months and to have principally a reproductive role.…”
Section: Discussionmentioning
confidence: 99%